1991
DOI: 10.1002/em.2850180420
|View full text |Cite
|
Sign up to set email alerts
|

Validation studies with Muta™ mouse: A transgenic mouse model for detecting mutations in vivo

Abstract: MutaMouse is a transgenic mouse engineered to detect mutations in vivo in any tissue of choice by using simple laboratory methods. The target is a bacterial lacZ gene incorporated via lambda phage into the genome of each mouse cell such that a concatamer of approximately 40 copies exists at a single site on both chromosomes of a homologous pair. In order to assess the potential usefulness of MutaMouse in detecting in vivo mutagenesis, several known mutagens/carcinogens were applied to male animals of 8-10 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…The Muta™Mouse and Big Blue ® Mouse are commercially available and appear to be the most efficient for in vivo mutational studies [Gossen et al, 1989;Kohler et al, 1991;Myhr, 1991]. Nevertheless, each system has limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The Muta™Mouse and Big Blue ® Mouse are commercially available and appear to be the most efficient for in vivo mutational studies [Gossen et al, 1989;Kohler et al, 1991;Myhr, 1991]. Nevertheless, each system has limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, mouse strains containing bacterial transgenes have made it possible to detect mutation in any tissue or cell type (1)(2)(3). Although dose-dependent increases in mutation frequency have been detected in several tissues (1)(2)(3)(4), there are several reasons to be concerned that a transgenic locus and a host locus may not respond alike. First, the location of the transgene can affect transgene expression (5) and mutational response.…”
mentioning
confidence: 99%
“…The doses of carcinogen used and the mutation frequencies induced in the liver with acute and subchronic regimens, in comparison to the carcinogenic potencies of the test compounds, are summarised in Table 2. As the data base is relatively small at this time, liver data from lacZ mice from Hazelton, Kensington, MD, USA (Myhr, 1991;Hoorn et al, 1993) The lowest dose giving rise to a significant effect is shown. a TD 511 is defined as the daily dose of a chemical (per kg body weight per day) that results in a 50% tumour incidence in Iabaratory animals after lifetime exposure (2 years in rats or mice).…”
Section: Resultsmentioning
confidence: 99%
“…However, in · the acute sturlies with chlorambucil (Hoorn et al, 1993), ethyl-and methylnitrosourea (Myhr, 1991;Kohl er et al, 1991a), doses lay in the acutely Iethai range (e.g., LD 50 of chlorambucil ~ 20 mgjkg). Taxicity can result in regenerative hyperplasia, whieh in turn can aceeierate the accumulation of mutations.…”
Section: Resultsmentioning
confidence: 99%